INDUSTRIAL BIOTECHNOLOGY-A SUSTAINABLE FUTURE - M. MURUGAN,; J. ALBINO WINS, (International Journal of Pharma and Bio Sciences, 2010)
Modern biotechnology refers to the application of biological organisms, systems and processes to the provision of goods and services. It uses enhanced microorganisms, like yeast, moulds and bacteria as “cell- factories” along with the enzymes derived from them to produce variety of goods. Use of renewable resources is very closely bound to the fossil raw materials that might replace and suffers when oil is relatively cheap. This review focuses on use of biotechnology for production of some bio products.